2016
DOI: 10.1371/journal.pone.0163077
|View full text |Cite
|
Sign up to set email alerts
|

Social Involvement Modulates the Response to Novel and Adverse Life Events in Mice

Abstract: Epidemiological findings suggest that social involvement plays a major role in establishing resilience to adversity, however, the neurobiology by which social involvement confers protection is not well understood. Hypothesizing that social involvement confers resilience by changing the way adverse life events are encoded, we designed a series of behavioral tests in mice that utilize the presence or absence of conspecific cage mates in measuring response to novel and adverse events. We found that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We next asked: how soon after placement in the PhenoTyper environment do isolated mice decrease their activity? Based on our prior observations (Colnaghi et al., 2016), we hypothesized that the effect of social isolation would have an immediate effect on locomotion. We measured distance traveled and time spent moving in the first 5 min after the mice were placed in the PhenoTyper, during the light cycle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next asked: how soon after placement in the PhenoTyper environment do isolated mice decrease their activity? Based on our prior observations (Colnaghi et al., 2016), we hypothesized that the effect of social isolation would have an immediate effect on locomotion. We measured distance traveled and time spent moving in the first 5 min after the mice were placed in the PhenoTyper, during the light cycle.…”
Section: Resultsmentioning
confidence: 99%
“…One such basic cue is the presence of peers. Based on our previous research demonstrating that mice tend to move less when facing adverse or novel experiences in the absence of conspecifics, we reasoned that the absence of a cage mate in the home cage environment will result in a decrease in locomotion similar to the responses to other anxiogenic contexts that we have previously characterized (Colnaghi et al., 2016). Indeed, we found that socially isolated mice have a lower level of activity compared to paired mice, and that this reduction is reversible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Squirrel monkeys exhibit ameliorated stress responses after exposure to a fearful stimulus (a snake) if social companions were present during exposure [26]. In rats, stress responses to fearful stimuli were reduced in the presence of a same-sex partner [27,28], and in mice, the presence of cage-mates reduces anxiolytic responses to novel and aversive stimuli [29].…”
Section: Introductionmentioning
confidence: 99%